Role of multimedia technologies in students’ independent work in conditions of distance learning - Nikitenko, Olga; Malyk, Yuliana (My University, 2022)
Currently during the period of the pandemic unsteady social and economic conditions and new educational priorities related to changing educational paradigms set the transition from reproductive forms and methods of teaching to individual and creative ones. Recently, when many higher scools throughout Ukraine were necessitated to apply the remote form of learning and teaching, the university curriculum has provided a very limited number of academic hours for foreign languages and at one time has given the students possibility to study more independently. At the same time, the flow of educational information is increasing and the number of academic hours does not provide any opportunity to cover all aspects of foreign language learning and equip future professionals with all the knowledge and skills that will make them competitive in an increasingly globalized world. As a result, the preference is now given to active teaching methods, which are aimed at developing students' independence, flexibility, variability, critical thinking.

Зараз у період пандемії нестабільні соціально-економічні умови та нові освітні пріоритети, пов’язані зі зміною освітніх парадигм, зумовлюють перехід від репродуктивних форм і методів навчання до індивідуально-креативних. Останнім часом, коли у багатьох вищих навчальних закладах по всій Україні виникла необхідність застосовувати дистанційну форму навчання та викладання, навчальний план університету передбачає дуже обмежену кількість академічних годин на вивчення іноземних мов і свого часу дає можливість студентам навчатися більш самостійно. У той же час потік освітньої інформації зростає, а кількість академічних годин не дає можливості охопити всі аспекти вивчення іноземних мов і озброїти майбутніх фахівців усіма знаннями та навичками, які зроблять їх конкурентоспроможними в умовах дедалі більшої глобалізації. світ. У зв’язку з цим зараз перевага надається активним методам навчання, які спрямовані на розвиток самостійності, гнучкості, варіативності, критичного мислення студентів.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; distance learning; students’ independent work; active teaching methods; multimedia technologies; дистанційне навчання; самостійна робота студентів; методи навчання; мультимедійні технології